Cromatografía de afinidad con péptidos como ligandos aplicada a la purificación del anticuerpo monoclonal terapéutico Bevacizumab - Barredo Vacchelli, Gabriela R. (2022)
Bevacizumab is widely used in cancer therapies due to its antiangiogenic power resulting from its\nbinding to vascular endothelial growth factor (VEGF). Its industrial purification process is based on\naffinity chromatography with immobilized protein A. The high cost and lability of the ligand, added to\nthe drastic conditions necessary to elute and recover the mAb, motivate the development of\nalternative ligands. In addition, conventional chromatographic matrices present mass transfer\nresistance and require prior clarification of the sample. The objective of this Thesis was to design\nsystems for the purification of bevacizumab based on short peptide of lower cost and with a longer\nuseful life compared to current systems based on protein A. From the screening of a peptide library\nand studies of the interaction site between bevacizumab and VEGF, peptide ligands were designed.\nThey were immobilized on chromatographic matrices and they were able to purify the mAb under\nmoderate conditions, protecting both the integrity of the biopharmaceutical and the chromatographic\nmatrix. The selected ligand, Ac-PHQGQHIGVSK, was immobilized also on magnetic nanoparticles. Those\nparticles allowed to purify bevacizumab and could be applied to unclarified samples.